Measuring Concentrations of Dissolved Methane and Ethane and the 13C of Methane in Shale and Till. Issue 1 (1st August 2016) - Hendry, M. Jim; Barbour, S. Lee; Schmeling, Erin E.; Mundle, Scott O. C.
Abstract: Baseline characterization of concentrations and isotopic values of dissolved natural gases is needed to identify contamination caused by the leakage of fugitive gases from oil and gas activities. Methods to collect and analyze baseline concentration‐depth profiles of dissolved CH4 and C2 H6 and δ 13 C‐CH4 in shales and Quaternary clayey tills were assessed at two sites in the Williston Basin, Canada. Core and cuttings samples were stored in Isojars ® in a low O2 headspace prior to analysis. Measurements and multiphase diffusion modeling show that the gas concentrations in core samples yield well‐defined and reproducible depth profiles after 31‐d equilibration. No measurable oxidative loss or production during core sample storage was observed. Concentrations from cuttings and mud gas logging (including IsoTubes ® ) were much lower than from cores, but correlated well. Simulations suggest the lower concentrations from cuttings can be attributed to drilling time, and therefore their use to define gas concentration profiles may have inherent limitations. Calculations based on mud gas logging show the method can provide estimates of core concentrations if operational parameters for the mud gas capture cylinder are quantified. The δ 13 C‐CH4 measured from mud gas, IsoTubes ®, cuttings, and core samples are consistent, exhibiting slight variations that should not alter the implications of the results in identifying the sources of the gases. This study shows core and mud gas techniques and, to a lesser extent, cuttings, can generate high‐resolution depth profiles of dissolved hydrocarbon gas concentrations and their isotopes. Abstract : Article impact statement : Methods to generate profiles of dissolved methane and ethane concentrations and the carbon isotopes of methane in argillaceous shales and tills are assessed.